A Cable-Net and Fabric Formwork System for the Construction of Concrete Shells: Design, Fabrication and Construction of a Full Scale Prototype. (April 2019) - Méndez Echenagucia, Tomás; Pigram, Dave; Liew, Andrew; Van Mele, Tom; Block, Philippe
Abstract: This paper describes the construction of a thin-shell concrete roof with a novel cable-net and fabric formwork system. The system consists of a fabric shuttering installed on a cable-net structure, which is tensioned from stiff boundary beams supported by standard scaffolding props. The cable-net is made from 2015 uniquely sized cables and rods, connected by 953 steel nodes. A specific non-uniform distribution of prestress was computed, such that under the weight of the wet concrete the cable-net sags into the desired shape of the final concrete shell. All of the elements of the formwork system were digitally fabricated by specialised industry partners in Switzerland. After the installation of the boundary structure, the cable-net was tensioned with the prescribed non-uniform prestress. An on-site shape control system was used to minimise deviations between the as-built geometry and the digital model. Starting from the lower supports, the concrete was sprayed on the flexible formwork from two aerial platforms in a carefully planned sequence. The construction of the shell together with partners from industry was a proof-of-concept demonstration of the formwork system, showing that concrete shells with complex doubly curved geometry can be built efficiently and with minimal material waste in a real-world context.